The Paradigm of Distributive Justice in Sharia Economics: A Qualitative Study of Changing Consumption Patterns in Modern Muslim Communities - Alghifari, Muhammad Azmi; Muthoifin, Muthoifin; Pramesty, Icha (Universitas Muhammadiyah Surakarta, 2025)
The transformation of contemporary Muslim consumption behavior is a phenomenon that cannot be separated from the influence of globalization, modernization, and consumerism culture. This condition poses its own challenges for the application of the distributive justice paradigm which is a fundamental principle in the sharia economy. Objective: This study aims to examine the distributive justice paradigm in sharia economics and explore its relevance to the transformation of modern Muslim consumption behavior. Methods: This study uses a qualitative method with a library research type, through analysis of normative sources and relevant scientific literature. The data analysis technique was carried out in a descriptive-interpretive manner by examining the concepts, values, and dynamics of consumption from the perspective of sharia economics. Results: The results of the study indicate that distributive justice in the sharia economy is not solely oriented to the mechanism of wealth distribution, but also demands the internalization of consumption ethics that are fair, balanced, and benefit-oriented. However, the consumption behavior of modern Muslims tends to shift towards excessive and symbolic consumption, potentially creating a gap between the normative values of Islamic economics and real consumption practices. This research emphasizes the importance of strengthening awareness of consumption ethics as an integral part of efforts to realize distributive justice in the context of modern Muslim society.